The promise and realities of Pay for Success/ Social Impact Bonds - Kenneth J. Saltman (Arizona State University, 2017)
This article considers proponents' arguments for Pay for Success also known as Social Impact Bonds. Pay for Success allows banks to finance public services with potential profits tied to metrics. Pay for Success has received federal support through the Every Student Succeeds Act of 2016 and is predicted by 2020 to expand in the US to a trillion dollars. As school districts, cities, and states face debt and budget crises, Pay for Success has been advocated by philanthropists, corporate consulting firms, politicians, and investment banks on the grounds of improving accountability, cost savings, risk transfer, and market discipline. With its trailblazing history in neoliberal education, Chicago did an early experiment in Pay for Success. This article provides a conceptual analysis of the key underlying assumptions and ideologies of Pay for Success. It examines the claims of proponents and critics and sheds light on the financial and ideological motivations animating Pay for Success. The article contends that Pay for Success primarily financially benefits banks without providing the benefits that proponents promise. It concludes by considering Pay for Success in relation to broader structural economic considerations and the recent uses of public schooling to produce short-term profit for capitalists.